2004
DOI: 10.1353/lan.2004.0024
|View full text |Cite
|
Sign up to set email alerts
|

Subjects and Interface Delay in Child Spanish and Catalan

Abstract: I observe that in an earlystage of child Catalan and Spanish, no overt subjects are used. At this same age and MEAN LENGTH OF UTTERANCE (MLU), child speakers of overt subject languages such as French, German, Dutch, and English use at least some overt subjects optionally. I explain this crosslinguistic variation bysuggesting that the adult target grammars vary with respect to the position in which overt subjects are realized. In the overt subject languages, subjects are realized in the canonical specifier-of-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
100
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(119 citation statements)
references
References 34 publications
10
100
1
1
Order By: Relevance
“…In (53) we have some examples from Hyams & Wexler (1993): (53) Want go get it Show Mommy that Not making muffins Thus, even children acquiring non-null-subject languages like English do not always produce full SV structures. Further, a delay in the production of appropriate preverbal subjects in other languages has also been recently noted (Casielles et al 2006, Grinstead 2004, Westergaard 2008. If supported by further research these studies would confirm the intrinsic complexity of these apparently simple SV structures.…”
supporting
confidence: 59%
“…In (53) we have some examples from Hyams & Wexler (1993): (53) Want go get it Show Mommy that Not making muffins Thus, even children acquiring non-null-subject languages like English do not always produce full SV structures. Further, a delay in the production of appropriate preverbal subjects in other languages has also been recently noted (Casielles et al 2006, Grinstead 2004, Westergaard 2008. If supported by further research these studies would confirm the intrinsic complexity of these apparently simple SV structures.…”
supporting
confidence: 59%
“…Grinstead (2004) found that children speaking Spanish and Catalan use subject with non-verbal predicates. Blom & Geert (2004) argue that children first go through a stage where they overdrop subjects in finite sentences.…”
Section: Studies In Other Languagesmentioning
confidence: 99%
“…Bel"s finding, that children converge early on the possibility of both null and overt subjects and that they differentiate between the two in an apparently adult-like way, is partially at odds with the results of Grinstead (2004), who finds that children go through a period of using only null subjects first and develop overt subjects later. Nonetheless, the Spanish-speaking children in Grinstead"s study still show relatively early convergence on the full range of possibilities for subjects, with preverbal overt subjects first appearing between 1;10 and 2;1 (and between 1;10 and 2;4 with the Catalan-speaking children).…”
mentioning
confidence: 90%
“…The only study where we have direct information on the relative timing of the acquisition of subject properties and the acquisition of wh-movement is Grinstead (2004). The Spanish-speaking children in his study begin using overt preverbal subjects between 1;10 and 2;1, but they apparently do not begin performing wh-movement until at least 2;3 -2;5, since none of them have given evidence of wh-movement by the time of their final file (between 2;2 and 2;4).…”
Section: Timing Of the Acquisition Of Subjects And Wh-questions In Chmentioning
confidence: 99%